(untitled) (Altre Modernità, 2015)
I consider the life of Georgia O’Keeffe (1887-1986), American Modernist painter and writer, as a series of windows through which she looks at the world and, at different stages, force and nourish the conquest of her identity as American, woman and artist. From the places of her childhood to the opaque period of ’confine’ in New York, as Stieglitz’s wife and woman-artist, O’Keeffe plans her evasion, looking for a space of her own where to find the center of her individuality. The opening to the world is embodied in the multiple perspectives that New Mexico offers, in its physical and mental spaces. At Ghost Ranch, and in Abiquiu, O’Keeffe finds the natural sources of a work that brings back originality and discipline. The present work, articulated within visual studies, literature and culture, considers O’Keeffe’s modernism from a new transcendentalist perspective. The analysis is based on a selection of letters between O’Keeffe and Stieglitz (1913-1946), O’Keeffe and Maria Chabot (1941-1949), on his autobiography (1976), and conversations recorded in C.S.Merril’s Weekends with O’Keeffe (1973-1979), supported by selected images. I assert that the windows in New Mexico, even if only virtually told in letters, ’mimetic’ and ’simulacral’, as in Friedberg’s The Virtual Window, turn out as bold openings in communion with the surrounding nature, and allow the artist to create the necessary exchange to live a collective individuality. O’Keeffe learns that this opening is the vehicle to honor her mission, the filter to better understand herself, protected by the reassuring domesticity, and the positive role model that, in the variations and repetitions of the simplicity of the daily rituals, restores her original relationship with the universe.